Dependent and independent causes of hypercalcemia - Rahman, Rahmathulla Safiyul; Al-Saffar, Hussain Fuad; Alasiri, Omar Abdu; Alata, Nada Jameel; Almalki, Abdulaziz Abdulmajeed; Althenayan, Mohammad A. J.; Althubaity, Mohammad Mulaihan; AlGhammas, Saleh Ibrahim; Alsubhi, Lojain Suweelim; Alwaheed, Baqer Mohammedsaeed; Almomen, Farah Abdulkareem (International Journal Of Community Medicine And Public Health, 2022)
Previous clinical studies show that the condition is significantly associated with mortality and increased cardiovascular morbidities. Accordingly, it is essential to conduct adequate diagnosis and evaluation to assess these cases properly. Studies show that different etiologies have been associated with hypercalcemia development with variable prevalence rates among different populations. Reduced PTH levels among patients with hypercalcemia indicate the presence of a non-PTH-dependant etiology for hypercalcemia. We have discussed various causes of hypercalcemia, including dependant and non-dependant causes. We found that malignancy-induced hypercalcemia is the commonest non-PTH-dependant etiology of hypercalcemia. Many malignancies were reported in the literature to attribute to the development of hypercalcemia. Vitamin D-mediated hypercalcemia was also reported as another common etiology for the condition. It might occur secondary to overdosing, immobilization, endocrine disorders, and granulomatous diseases. Other familial and congenital causes were also reported in the literature and discussed.